2020
DOI: 10.47067/reads.v6i2.198
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Fear Through Media: Analysis to Reveal Relationship between Perception about COVID 19 and Socio-economic Background of Media Consumers

Abstract: COVID-19 is the pandemic that has been experienced by the whole world presently. The present research sought to explore how media is cultivating fear among heavy and light users of upper, middle, and lower socio-economic background. Theoretical support for the present research was taken from the theory of cultivation analysis. Twenty-one residents of Multan belonging to upper, middle and lower socio-economic background were selected through snowball sampling technique and interviewed through WhatsApp by the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Studies on the ways in which the media have handled the COVID-19 pandemic have already accounted for some important aspects, including the biases that characterise mass information [45] (AlAfnan, 2020), among which stigma and incitement to hatred emerge in importance [46] (Robie, Krishnamurthi, 2020), but have also underlined the ability to give scientifically correct information [47] (Anderson et al, 2021). They then considered effects from the resulting increase in perceived risk of contagion as well, including depression [48] (Olagoke et al, 2020), worry and fear [49,50] (Garfin et al, 2020; Manzoor & Safdar, 2020). Despite all these contributions, to date there is very little literature regarding how the press has addressed the current pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the ways in which the media have handled the COVID-19 pandemic have already accounted for some important aspects, including the biases that characterise mass information [45] (AlAfnan, 2020), among which stigma and incitement to hatred emerge in importance [46] (Robie, Krishnamurthi, 2020), but have also underlined the ability to give scientifically correct information [47] (Anderson et al, 2021). They then considered effects from the resulting increase in perceived risk of contagion as well, including depression [48] (Olagoke et al, 2020), worry and fear [49,50] (Garfin et al, 2020; Manzoor & Safdar, 2020). Despite all these contributions, to date there is very little literature regarding how the press has addressed the current pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…This study provides a preliminary exploration of potential key antecedents of mental resilience of employees and risk factors for the occurrence of mental disorders under prolonged stress exposure. While most studies on risk communication are focused on the influence of media on employees response formation (Chong and Choy, 2018 ; Garfin et al, 2020 ; He et al, 2020 ; Manzoor and Safdar, 2020 ; Tsoy et al, 2021 ), we have undertaken to investigate how threat perception and perceived efficacy under the ongoing exposure to job uncertainty can precipitate mood disorders. There is lack of support in the literature that would explain how exposure to hazard-related information influences the formation of adaptive or maladaptive coping strategies of employees aimed at psychological well-being retention.…”
Section: Introductionmentioning
confidence: 99%
“…Through their storytelling function, the media also have the capacity to cultivate certain beliefs, perspectives, values, and attitudes, thereby shaping culture and perceptions of the world ( 17 ). In the case of the COVID-19 pandemic, researchers have suggested that the media have shaped public risk perception ( 18 ), trust and mistrust ( 19 ), fear ( 20 ), and compliance with public health measures ( 11 , 21 ). For the general public, media reporting on COVID-19 has allowed for the swift dissemination of information in ways that are more accessible than research findings, which often take significant time to produce and are written for a select audience.…”
Section: Discussionmentioning
confidence: 99%